Accuracy Analysis of Indoor Positioning Using Min-Max Method - Pichaya Supanakoon; Wipassorn Vinicchayakul; Sirinya Tabsombat; Thanadol Tiengthong; Sathaporn Promwong; Monchai Chamchoy (My University, 2025)
In this paper, the accuracy analysis of indoor positioning using min-max method is proposed. The distance error model is applied to estimate the distance between the transmitter and user's position with different path loss exponent and fading amount of indoor channel. The total $\mathbf{1 0 0}$ coordinates of user's positions are estimated using min-max method. The distance error at each position, probability density function (PDF) and cumulative distribution function (CDF) of distance errors are illustrated. The mean of analysis distance error corresponds with the mean of measurement distance error with same path loss exponent and fading amount of indoor channel. The results show that it is possible to use this accuracy analysis to estimate the distance error in an indoor environment.
Keywords: Indoor and Outdoor Localization Technologies